A methodology for wellbore stability analysis of drilling into presalt formations: A case study from southern Iran - Gholami, Raoof; Rabiei, M.; Aadnoy, B.; Rasouli, V. (Elsevier, 2018)
Drilling into presalt formations has been a long-standing issue due to the rapid changes in the diameter of the borehole during drilling operations either because of creep or wash-out dissolution. There have been many studies on characterization of salts, with many mathematical models being presented to estimate the pressure induced due to the squeezing salt sheets. However, the results of none of these models have been fully validated against real field data and some recommendations have been made based on numerical simulations. In this study, attempts were made to introduce a methodology based on damage mechanics for wellbore stability analysis of a wells drilled in the southern part of Iran. The results obtained indicated that the presence of a thick salt layer in the well has resulted in significant wellbore closure in the intervals above the reservoir section. It was also found that the salt exhibits viscoelastic behaviour during drilling due to the homogeneous temperature which has not reached the threshold limit of viscoplastic boundary. A complicated change in the stress regime was also observed which could be linked to the existence of the thick salt layer or presences of a fault crossing the well. Therefore, it is recommended to further validate this model in other wells using the methodology presented.